2021
DOI: 10.3390/agronomy11091853
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Nourishment with Different Zinc-Containing Forms Effectively Sustains Carrot Performance in Zinc-Deficient Soil

Abstract: Among the essential micronutrients, zinc (Zn) affects vital functions in crop plants. The influences of foliar nourishing with certain Zn-containing forms on the growth, productivity, and physiology of carrot plants (cv. Fire wedge F1) and their nutritional contents when grown in Zn-deficient soil were examined in both 2019/2020 and 2020/2021 field trials. Two doses of zinc oxide nanoparticles (ZnO-NPs(1) = 20 and ZnO-NPs(2) = 40 mg L−1), zinc–EDTA (Zn–EDTA(1) = 1 and Zn–EDTA(2) = 2 g L−1), or bulk zinc oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…There is less knowledge about what happens in plants after the application of foliar fertilizer. Awad et al [35] stated that zinc-containing foliar fertilizer significantly increases the relative chlorophyll content in carrot leaves under zinc-deficient conditions. In addition, other research studies showed the positive effect of zinc foliar fertilization on the chlorophyll content of citrus [36] and canola [37] under zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…There is less knowledge about what happens in plants after the application of foliar fertilizer. Awad et al [35] stated that zinc-containing foliar fertilizer significantly increases the relative chlorophyll content in carrot leaves under zinc-deficient conditions. In addition, other research studies showed the positive effect of zinc foliar fertilization on the chlorophyll content of citrus [36] and canola [37] under zinc deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Egypt is a developing country, which mainly depends upon agriculture as a main source of foods [1]. Despite the tremendous progress in the development of this sector, in recent decades, extreme population growth has become the main obstacle toward achieving the objectives of sustainable agriculture development [2] compared with other factors such as the conservation of soil, water, and animal and plant genetic resources, in addition to organic agriculture, integrated agricultural production, agroforestry production, and crop-livestock-forest integration.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, more than one billion people currently suffer from hunger, and about 33 countries in the developing world have extremely alarming hunger levels [2]. Egypt is a developing country that suffers from food insecurity resulting from extreme population growth [3] alongside limited agricultural land. Generally, economic development is significantly dependent on the agricultural sector, which represents 40% of the Egyptian workforce in Egypt.…”
Section: Introductionmentioning
confidence: 99%